2023
DOI: 10.1111/opo.13234
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ocular astigmatism with age: A longitudinal study

Jeremy Beesley,
David B. Elliott

Abstract: PurposeTo investigate changes in astigmatism with age. Are changes from with‐the‐rule (WTR) in younger ages to against‐the‐rule (ATR) in older patients mediated through oblique astigmatic axes or spherical prescriptions, and at what ages do these changes occur?MethodsPrescription data were gathered retrospectively from one optical practice belonging to a large multiple group in the UK. Longitudinal assessments were made of the changes in astigmatism for 326 patients (mean age at first prescription 46 years, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Changes in ocular astigmatism with age have been previously well-documented. Most eyes (55%) do not undergo astigmatic changes (in cylinder power or axis) until their mid-40s with many (41%) not experiencing a change until after their mid-50s [ 4 ]. This transformation is characteristically a conversion from with-the-rule (WTR) to against-the-rule (ATR) astigmatism, which studies have shown are three times more likely to rotate through oblique axes to return as ATR rather than reducing to zero and re-emerging as ATR [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in ocular astigmatism with age have been previously well-documented. Most eyes (55%) do not undergo astigmatic changes (in cylinder power or axis) until their mid-40s with many (41%) not experiencing a change until after their mid-50s [ 4 ]. This transformation is characteristically a conversion from with-the-rule (WTR) to against-the-rule (ATR) astigmatism, which studies have shown are three times more likely to rotate through oblique axes to return as ATR rather than reducing to zero and re-emerging as ATR [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most eyes (55%) do not undergo astigmatic changes (in cylinder power or axis) until their mid-40s with many (41%) not experiencing a change until after their mid-50s [ 4 ]. This transformation is characteristically a conversion from with-the-rule (WTR) to against-the-rule (ATR) astigmatism, which studies have shown are three times more likely to rotate through oblique axes to return as ATR rather than reducing to zero and re-emerging as ATR [ 4 ]. Male eyes also exhibit greater and earlier ATR corneal astigmatism compared to female eyes, a sex-related difference with potentially significant implications for astigmatism correction [ 5 ].…”
Section: Introductionmentioning
confidence: 99%